A synchronic comparison between the vowel phonemes of Bengali & English phonology and its classroom applicability - Tamzida, Aleeya; Siddiqui, Sharmin (Stamford Journal of English, 2013)
Due to linguistic diversity, phonologies of the world are notably different from one another, leading the foreign language learners encounter varied phonetic and phonological problems. Bengali speaking EFL learners face problems especially in pronunciation owing to their lack of sound knowledge regarding the distinct positions of phonemes and other aspects of Bengali and English phonology. In this context, our attempt, particularly in this article, is to compare the positions of Bengali and English vowel phonemes and identify the distinctions existing between those in order to help the Bengali speaking EFL learners to improve their pronunciation. Mainly, English vowels (RP) Diagram, Bengali vowels diagram, Cardinal vowels diagram etc have been examined to identify the distinctions mentioned. This paper shows the applicability of our findings by presenting some survey results and suggests some measures to be followed by learners to improve their pronunciation. Stamford Journal of English; Volume 6; Page 285-314 DOI: http://dx.doi.org/10.3329/sje.v6i0.13919